Organoid scaffold materials: research and application - Zhang, Ziwei; Zhu, Maoshu; Luo, Haiqing; Zeng, Fanwei; Qi, Zhongquan (Frontiers in Bioengineering and Biotechnology, 2025)
In recent years, organoid research has witnessed remarkable progress, yet significant challenges remain in organoid construction. As fundamental architectural frameworks, organoid scaffolds play a pivotal role in facilitating three-dimensional tissue morphogenesis by delivering crucial biochemical and mechanical signals during in vitro organoid development. A systematic examination of scaffold functions in organoid culture systems, coupled with a critical assessment of different scaffold modalities, not only deepens our understanding of organoid biology and their microenvironment but also provides valuable insights for next-generation scaffold design. This review elucidates the fabrication principles and applications of organoid scaffolds, delineates their functional significance in organoid culture, categorizes existing scaffold systems with comparative analysis of their respective merits and limitations, and concludes with perspectives on future research directions in scaffold development.